Pendidikan Komunikasi Interkultural dan Pluralitas: Membangun Toleransi Antar Umat Beragama - Syatriadin (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
This paper attempts to describe the effectiveness of intercultural communication in building thoughts and attitudes toward the plurality of tolerance among religious communities, as well as to provide an overview of the concept of intercultural communication and the concept of plurality of religious tolerance. This study is a literature study through the work of other researchers obtained through journals, books, and the internet. The results of the study show that the concept of intercultural communication has a relationship in building people's perceptions, attitudes, and actions in carrying out life activities in a socio-religious context. Communication is a medium for establishing ties between religious communities. The integration between tolerance and plurality is constructed in a system of religious harmony and harmony based on human attitudes in communicating, including several attitudes shown when individuals are present and internalize external events including denial, defense, minimization, acceptance, adaptation, and integration. This process will certainly be faced by each individual with various attitude criteria shown including being exclusive, inclusive, and pluralist. Thus tolerance comes with effective and efficient communication and provides a positive view of every ethnic, racial, cultural, and religious entity.